The impact of COVID-19 pandemic on the Emergency Room and Orthopedic Departments in Piacenza: a retrospective analysis - Maniscalco, Pietro; Ciatti, Corrado; Gattoni, Serena; Puma Pagliarello, Calogero; Moretti, Giorgio; Cauteruccio, Michele; Carpaneto, Diana; Capelli, Patrizio; Gurrieri, Luca; Banchini, Filippo; Quattrini, Fabrizio (Acta Biomedica Atenei Parmensis, 2020)
Introduction and Aim: The Coronavirus pandemic represents one of the most massive health emergencies in the last century. Aim of the study is to evaluate the trend of E.R. accesses and orthopaedic events during the pandemic of Covid-19.Materials and Methods: we retrospectively analysed all data related to patients admitted to the E.R. Department of the Hospital of Piacenza from August 26th 2019 to August 23rd 2020, splitting this period on February 23rd 2020.Results: Our analysis shows a reduction of -18.0% in E.R. accesses. We calculated a growth of deaths in the E.R. equal to +220%. Our orthopaedic pathway recorded a drop of -26.8%. Traumas occurred at home increased (+19.1%). We note an actual drop only on proximal femur fractures (weighted average of -17.7%), while all the others underwent an increase.Discussion: The amount of E.R. accesses registered a drop -18.0%, while the pathway dedicated to emergency cases underwent an increase. The major complexity of clinical conditions influenced the number of hospitalizations and the fear of the infection increased hospitalization refusals. There has been a zeroing of school traumas, a reduction in sport, transfer home-work/work-home, work, roadside, injuries. Total amount of fractures strongly increase after the end of the lockdown.Conclusion: our data confirmed the decrease of retirement houses, sports, works and roadsides traumas and a zeroing of schools ones, while those occurred inside domestic environment underwent a consistent raise. We noticed a reduction in femur fractures and significant spread of all fractures after the end of the lockdown.